Rare Potamogeton species can establish in restored Danish lowland stream reaches - Johnsen, Trine Just; Henriksen, Lisbeth Dalsgaard Romme; Larsen, Mette Bundgaard; Kallestrup, Helena; Larsen, Søren Erik; Riis, Tenna; Baattrup‐Pedersen, Annette (Freshwater biology, 2022)
Freshwater biodiversity is severely threatened, and despite many efforts to halt biodiversity loss the decline continues. Here, we used a transplantation approach to explore whether failure to reverse this trend for freshwater plants reflects that restoration measures applied to streams are inadequate for restoring suitable habitat conditions for plant species in decline. We identified declining species within the plant genus Potamogeton and introduced five of these (Potamogeton compressus L., Potamogeton gramineus L., Potamogeton lucens L., Potamogeton praelongus Wulfen., and Potamogeton pusillus L.) into five restored lowland stream reaches in three different habitat types to examine species establishment and growth. We found that plant establishment varied among streams and species, but we did not see any effect of habitat type within streams on either species growth or survival. Potamogeton compressus and P. pusillus failed to overwinter, while P. gramineus, P. lucens, and P. praelongus were all able to establish viable stands and to overwinter successfully in several of the experimental streams. Our results suggest that suitable habitats are available for declining Potamogeton species in restored stream reaches in Denmark, but their continued growth may be challenged by limited overwintering success. Consequently, we find it likely that dispersal constraints prevent declining Potamogeton species from naturally recolonising restored stream reaches. Understanding the importance of life history traits, such as overwintering and dispersal, can be crucial for the recovery of plant diversity in streams. Here we show that species that survived during winter were those with extensive growth of roots and rhizomes making them more adapted to withstand high flows than species relying on seeds and turions for overwintering. The creation of calmer backwater habitats can therefore be crucial when restoring stream reaches since these habitats may facilitate overwintering of species lost from the main channel during winter.